Being Needed but Hated: The Exodus of Dutch Scientists in Indonesia, 1945–1959 (KEMANUSIAAN The Asian Journal of Humanities, 2024)
The Japanese occupation in 1942 compelled Dutch scientists to depart from Indonesia or face imprisonment as prisoners of war. The Allied victory led to the liberation of captive scientists and encouraged Dutch scientists to return to Indonesia. This article aims to analyse and describe: (1) the process of Dutch scientists’ reentry to Indonesia in 1945 to 1949 and 1950 to 1959 and (2) the factors that caused the departure of Dutch scientists from Indonesia from 1949 to 1959. The archives at the National Archives of the Republic of Indonesia (ANRI) and the National Research and Innovation Agency (BRIN) are used as sources for this article. Dutch scientists are discussed more extensively since they were the most impacted by the dynamics of Indonesian nationalism. In 1945 to 1949, Dutch scientists had more opportunities than their Indonesian counterparts. However, the Dutch, including their scientists, were obliged to leave Indonesia in 1949 following the Konferensi Meja Bundar agreement. The exodus of Dutch scientists prompted the government to recruit scientists from various countries to fill vacant positions from 1950 to 1959. Nevertheless, bureaucratic inefficiency, different regulations regarding the supervision of foreigners and the emergence of anti-foreign sentiment in an unstable social, political and economic situation encouraged foreign scientists to return to their homeland.